Bedeutungsherstellung als Lehr- und Lerninhalt (mathematica didactica, 2021)
In this paper the so-called mathematical representations are considered as sign games in the meaning of Wittgenstein. In these sign-games, meaning appears as a result of the use of inscriptions due to given rules. By means of this approach, many phenomena of mathematics such as the possibility of multiple representations of so-called mathematical objects can be explained in a purely constructive way. In the course of the following considerations, advantages of this view are theoretically explained and made available for the practice of mathematics teaching by given examples.